A 3D FeOOH nanotube array: an efficient catalyst for ammonia electrosynthesis by nitrite reduction. Issue 33 (6th April 2022) - Liu, Qin; Liu, Qian; Xie, Lisi; Yue, Luchao; Li, Tingshuai; Luo, Yongsong; Li, Na; Tang, Bo; Yu, Lingmin; Sun, Xuping
Abstract : An FeOOH nanotube array supported on carbon cloth enables ambient electrochemical nitrite reduction to ammonia, achieving a large NH3 yield of 11937 μg h −1 cm −2 and a high faradaic efficiency of 94.7% in 0.1 M PBS with 0.1 M NO2 − . Abstract : Nitrite (NO2 − ) is a detrimental pollutant widely existing in groundwater sources, threatening public health. Electrocatalytic NO2 − reduction settles the demand for removal of NO2 − and is also promising for generating ammonia (NH3 ) at room temperature. A nanotube array directly grown on a current collector not only has a large surface area, but also exhibits improved structural stability and accelerated electron transport. Herein, a self-standing FeOOH nanotube array on carbon cloth (FeOOH NTA/CC) is proposed as a highly active electrocatalyst for NO2 − -to-NH3 conversion. As a 3D catalyst, the FeOOH NTA/CC is able to attain a surprising faradaic efficiency of 94.7% and a large NH3 yield of 11937 μg h −1 cm −2 in 0.1 M PBS (pH = 7.0) with 0.1 M NO2 − . Furthermore, this catalyst also displays excellent durability in cyclic and long-term electrolysis tests.